Heterogeneity of Pulmonary Granulomas in Cattle Experimentally Infected With Mycobacterium bovis - Palmer, Mitchell V.; Thacker, Tyler C.; Kanipe, Carly; Boggiatto, Paola M. (Frontiers in Veterinary Science, 2021)
Mycobacterium bovis is the cause of tuberculosis in most animals, most notably cattle. The stereotypical lesion of bovine tuberculosis is the granuloma; a distinct morphological lesion where host and pathogen interact and disease outcome (i.e., dissemination, confinement, or resolution) is determined. Accordingly, it is critical to understand host-pathogen interactions at the granuloma level. Host-pathogen interactions within individual granulomas at different stages of disease have not been examined in cattle. We examined bacterial burden and cytokine expression in individual pulmonary granulomas from steers at 30, 90, 180, and 270 days after experimental aerosol infection with M. bovis. Bacterial burdens within individual granulomas examined 30 days after infection were greater and more heterogenous (variable) than those examined 90 to 270 days after infection. Bacterial burdens did not correlate with expression of IFN-gamma, TNF-alpha, TGF-beta, granuloma stage, or lung lesion score, although there was a modest positive correlation with IL-10 expression. Granuloma stage did have modest positive and negative correlations with TNF-alpha and IL-10, respectively. Heterogeneity and mean expression of IFN-gamma, IL-10 and TNF-alpha did not differ significantly over time, however, expression of TGF-beta at 90 days was significantly greater than that seen at 30 days after infection.